Assessing Data Completeness, Quality, and Representativeness of Justifiable Homicides in the FBI’s Supplementary Homicide Reports: A Research Note - Finch, Brian Karl (Journal of quantitative criminology, 2022)
Introduction The most widely used data set for studying police homicides—the Supplementary Homicide Reports (SHR) kept by the Federal Bureau of Investigation—is collected from a voluntary sample. Materials and Methods Using a journalist-curated database of police-related deaths, we find the SHR police homicide data to be substantially incomplete. This is due to both non-reporting and substantial under-reporting by agencies. Further, our inquiry discloses a pattern of error in identifying “victims” and “offenders” in the data, and finds that investigating agencies are often incorrectly listed as the responsible agency, which seriously jeopardizes police department-level analyses. Finally, there is evidence of sample bias such that the SHR data system is not representative of all police departments, nor is it representative of large police departments. Conclusions We conclude that the SHR data is of dubious value for assessing correlates of police homicides in the United States, as all analyses using it will reflect these widespread biases and significant undercounts. Analysis of SHR data for these purposes should cease.